Using Concept Maps to compare obesity knowledge between policy makers and primary care researchers in Canada - Elizabeth Sturgiss; Thea Luig; Denise L. Campbell-Scherer; Richard Lewanczuk; Lee A. Green (BMC Research Notes, 2019)
Abstract Objective Knowledge transfer is the process of information sharing between researchers, knowledge users and policy makers. Globally, public policies about obesity do not reflect the complexity of what is known about the cause and effects of obesity. We used Concept Maps, a qualitative method that represents mental models, to compare the understanding of obesity between policy makers in a Canadian province and local primary care researchers. Eight participants were interviewed during which a Concept Map was developed using “C-map Tools” software. Maps were then colour-coded to identify themes and concepts in the maps. Finally, the team synthesised the findings from each of the maps and presented them back to each of the participants. Results All participants had mental models with rich details on the complexity of obesity for individuals, community, and at the policy level. Clinician-researchers had more focus on medical management than policy makers although most participants lacked concepts on the role of primary care in obesity management. A shared understanding of obesity could assist researchers and policy makers in developing a relevant and effective strategy. Concept Mapping provides a novel and creative way to visually compare different understandings of health-related topics.